(untitled) (Journal of Geography and Environmental Management, 2018)
The article presents an analysis of travel agencies require some changes. As a result of the analysis concluded that the trend in the tourism market in Kazakhstan goes to purchase travel products via online resources. A list of opportunities for companies selling tourist services and modern approaches to marketing policy. As the international market, and sales of tourist products in Kazakhstan the reform process is associated with the emergence of new intermediary organizations offering the sale of certain services. However, in Kazakhstan there is no single platform or platforms, which would provide the opportunity to complete tours. It is therefore recommended to create a tourist portal, which would simplify the buying process for consumers and has created the conditions for the organization of tourist companies of sales.